2006
DOI: 10.1093/brain/awl243
|View full text |Cite
|
Sign up to set email alerts
|

Striosomes and mood dysfunction in Huntington's disease

Abstract: Variable phenotype is common in neurological disorders with single-gene inheritance patterns. In Huntington's disease, mood and cognitive symptoms are variably co-expressed with motor symptoms. There is also variable degeneration of neurons in the two major neurochemical compartments of the striatum, the striosomes and the extrastriosomal matrix. To determine whether the phenotypic variability in Huntington's disease is related to this compartmental organization, we carried out a double-blind study in which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 55 publications
4
121
0
Order By: Relevance
“…Neurons from striosome and matrix compartments display differential activity during natural behaviour or following psychomotor stimulant treatments (Brown et al, 2002;Canales and Graybiel, 2000). Similarly, the specific loss of neurons from either compartment has been correlated with distinct clinical features in Huntington's disease (Tippett et al, 2007), while selective impairment of the function of either neuronal compartment can have different effects on motor function and behaviour (Tappe and Kuner, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Neurons from striosome and matrix compartments display differential activity during natural behaviour or following psychomotor stimulant treatments (Brown et al, 2002;Canales and Graybiel, 2000). Similarly, the specific loss of neurons from either compartment has been correlated with distinct clinical features in Huntington's disease (Tippett et al, 2007), while selective impairment of the function of either neuronal compartment can have different effects on motor function and behaviour (Tappe and Kuner, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The dysfunction of striatal matrix neurons is especially severe for the indirect pathway neurons of the striatum, which in the sensorimotor striatum receive powerful inputs from the motor cortex (4)(5)(6). In different models of parkinsonian states, the gradients and compartmental expression of dopaminergic deficits vary (7)(8)(9), but it seems likely that dysfunctional dopaminergic modulation of corticostriatal motor pathways leading through the matrix compartment is a major contributor to the motor symptoms of Parkinson's disease, and that in a range of movement disorders, compartmentally selective striatal dysfunction is present (10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Tippett et al (2007) observed that both directions of progression occur and that the heterogenic pattern is associated with the heterogeneity in clinical symptoms. Interestingly, the balance between striosomal and matrix loss was associated with the number of CAG repeats.…”
Section: Huntington's Disease Involves Targeted Cell Deathmentioning
confidence: 99%
“…The direction of neuropathology, from striosomal to matrix or the reverse, was shown to be correlated with mood changes (Tippett, et al, 2007). It is assumed that the dysfunctional striosomal STR-SNc loop underlies this pattern and involves the reinforcement learning system.…”
Section: A Classification Scheme For Tasks Used In Hd Researchmentioning
confidence: 99%